Digestibility and protein content improvement of corncob silage using chicken feather partially digested by Bacillus subtilis G8 - Chayatip Suttiniyom (2018)
© 2015 Friends Science Publishers. Chicken feather digestions by Bacillus subtilis G8 culture and crude keratinase were comparatively investigated. Digestion by crude keratinase released the soluble protein corresponding with the enzyme quantities used. The maximum soluble protein released by crude keratinase were 27 and 23% by weight from milled chicken feather (MCF) and un-milled chicken feather (UCF), while bacterial digestion released 51 and 43% from MCF and UCF, respectively. Partially digestion by bacterial culture was selected as the appropriate process based on total crude protein remaining, practicability and economic reasons. Using bacterial digested chicken feather (BDCF) as a protein source for corncob silage (CS) fermentation by mixing 5, 10 and 15% BDCF generated the BDCF mixed silages as CS-BDCF-5%, CS-BDCF-10% and CS-BDCF-15%, respectively. Proximate analysis revealed the proportionally increase of crude protein with the BDCF added. Crude protein of 33.46% was found in CS-BDCF-15%, while those of CS-BDCF-5% and CS-BDCF-10% were 14.12% and 25.02%, respectively. Gas production values from in vitro digestibility test of all BDCF mixed silages were not different significantly at 24 h, while in sacco digestibility of CS-BDCF-15% showed the highest value of dry matter degradation. This research confirms the advantage of BDCF and strongly supports potentiality to utilize CS-BDCF for ruminant feeding.